Computed Tomography Assessment of Hepatic Steatosis Using Liver Attenuation Index in Non-alcoholic Adults at a Tertiary Hospital in Nepal - Joshi, Ram Datt; Sah, Ramswarth; Khanal, Umesh Prasad; Thapa, Rossu; Swar, Avishek; Lamichhane, Suman; Joshi, Deepak Raj (Annapurna Journal of Health Sciences, 2026)
Introduction: Hepatic steatosis is the accumulation of intrahepatic fat of more than 5.00% of liver weight. The liver attenuation index, derived from non-contrast abdominal computed tomography, is a reliable quantitative tool for assessing liver fat content. The purpose of this study was to investigate the prevalence of hepatic steatosis using non-contrast enhanced computed tomography images in non-alcoholic, adults without known liver diseases and to assess the relationship of steatosis with age, gender, diet, and body mass index. Methods: This descriptive cross-sectional study was performed in 422 normal adults from August 2024 to February 2025. Data was collected on the baseline history of the patient and evaluation of computed tomography images, as normal. Liver and spleen attenuation values were measured at multiple segments of liver and spleen, and the computed tomography liver attenuation index was calculated. Data were analysed using SPSS version 27. The prevalence of hepatic steatosis was compared amongdifferent age, gender, diet,and body mass indexgroups by using the Chi-square and Fisher’s exact test at 5 % level of significance. Results: Among 422 participants, 70.10% had normal liver attenuation, 26.80% had mild-to-moderate steatosis, and 3.10% had severe steatosis. Hepatic steatosis showed a statistically significant association with body mass index (p<0.001) but not with age, gender, and dietary habits. Conclusions: This study concludes that hepatic steatosis is relatively common, and the likelihood of developing mild, moderate, or severe forms increases with higher body mass index.